Land Use Change Patterns In Massachusetts 2001-2011: A Case Study using NLCD land cover data - Liu, Jiao. (2018)
Abstract: This thesis will explore the utility of publicly available datasets specifically the National Land Cover Database (NLCD), Smart Location Database and MassGIS data to show ways in which urban planners and policy-makers in Massachusetts could better understand spatial land use change patterns and the correlation between land use change and built environment characteristics. In addition, the literature review provides an assessment of the use of NLCD data and a survey of existing research on how land use change is related to the built environment. The results suggest that a significantly large area changed to lower intensity developed urban area from forest in Massachusetts between 2001 and 2011. Land use change patterns were also significantly affected by the built environment of the location. Specifically, the regression models suggest that proximity to transit and transit-based accessibility to jobs were significant in making low-intensity land use change less likely and automobile-based access to jobs led to significantly higher low-intensity land use change. This thesis finds that NLCD, Smart Location and local GIS data like the data obtained from MassGIS, could be used to better understand the land use change patterns. Finally, it concludes with some limitations in data and methodology and suggestions for future research as well as some recommendations for planners and policy makers.; Thesis (M.A.)--Tufts University, 2018.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Sumeeta Srinivasan.; Committee: Barbara Parmenter.; Keywords: Land use planning, Geographic information science and geodesy, and Transportation.